2020
DOI: 10.1002/jmri.27311
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI in Cervical Cancer: Associations Between Imaging Biomarkers and Tumor Stage, Disease Progression, and Overall Survival

Abstract: Background: Positron emission tomography (PET)/MRI biomarkers have been shown to have prognostic significance in patients with cervical cancer. Their associations with progression-free survival (PFS) and overall survival (OS) merit further investigation. Purpose: To evaluate the association between PET/MRI biomarkers and tumor stage, PFS, and OS in patients with cervical cancer. Study Type: Prospective cohort study. Population: In all, 54 patients with newly diagnosed cervical cancer and measurable tumors (>1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In previous studies, mainly relying on PET/CT, the PET component often failed to provide additional locoregional staging information. In our quantitative analysis of the PET data, MTV was independently associated with higher T-stage, as well as with LARC, similar to what is known from other tumor entities, such as cervical or esophageal cancer [ 33 , 34 ]. Compared to MRI staging, MTV yielded an excellent sensitivity of 91.7% and specificity of 68.2% for LARC, significantly superior to anatomical MRI assessment.…”
Section: Discussionsupporting
confidence: 73%
“…In previous studies, mainly relying on PET/CT, the PET component often failed to provide additional locoregional staging information. In our quantitative analysis of the PET data, MTV was independently associated with higher T-stage, as well as with LARC, similar to what is known from other tumor entities, such as cervical or esophageal cancer [ 33 , 34 ]. Compared to MRI staging, MTV yielded an excellent sensitivity of 91.7% and specificity of 68.2% for LARC, significantly superior to anatomical MRI assessment.…”
Section: Discussionsupporting
confidence: 73%
“…Higher SUVmax values are often associated with a higher likelihood of metastatic spread to lymph nodes ( 21 ). Due to its susceptibility to noise and its inability to reflect the overall metabolic level of tumors, the SUVmax has limited value in predicting LNM or prognostic evaluation of cervical cancer ( 22 , 23 ). Additionally, physiological uptake of adjacent structures such as the ureter and bladder occasionally lead to increased FDG uptake in lymph nodes, or high FDG uptake in reactive hyperplasia lymph nodes, resulting in false positives.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have found that once one or more RNA in the ceRNA regulatory network are abnormally expressed, the homeostasis is destroyed, leading to disease occurrence (Torre et al, 2015). The current study focused on treatment and prediction in early and advanced cancer (Pontes et al, 2020;Shih et al, 2021). Understanding the molecular mechanism is of great significance for better diagnosis and treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%